Risperidone in the treatment of disruptive behavioral symptoms in children with autistic and other pervasive developmental disorders - Shea, Sarah; Turgay, Atilla; Carroll, Alan; Schulz, Miklos; Orlik, Herbert; Smith, Isabel; Dunbar, Fiona (Pediatrics (Evanston), 2004)
To investigate the efficacy and safety of risperidone for the treatment of disruptive behavioral symptoms in children with autism and other pervasive developmental disorders (PDD). In this 8-week, randomized, double-blind, placebo-controlled trial, risperidone/placebo solution (0.01-0.06 mg/kg/day) was administered to 79 children who were aged 5 to 12 years and had PDD. Behavioral symptoms were assessed using the Aberrant Behavior Checklist (ABC), Nisonger Child Behavior Rating Form, and Clinical Global Impression-Change. Safety assessments included vital signs, electrocardiogram, extrapyramidal symptoms, adverse events, and laboratory tests. Subjects who were taking risperidone (mean dosage: 0.04 mg/kg/day; 1.17 mg/day) experienced a significantly greater mean decrease on the irritability subscale of the ABC (primary endpoint) compared with those who were taking placebo. By study endpoint, risperidone-treated subjects exhibited a 64% improvement over baseline in the irritability score almost double that of placebo-treated subjects (31%). Risperidone-treated subjects also exhibited significantly greater decreases on the other 4 subscales of the ABC; on the conduct problem, insecure/anxious, hyperactive, and overly sensitive subscales of the Nisonger Child Behavior Rating Form (parent version); and on the Visual Analog Scale of the most troublesome symptom. More risperidone-treated subjects (87%) showed global improvement in their condition compared with the placebo group (40%). Somnolence, the most frequently reported adverse event, was noted in 72.5% versus 7.7% of subjects (risperidone vs placebo) and seemed manageable with dose/dose-schedule modification. Risperidone-treated subjects experienced statistically significantly greater increases in weight (2.7 vs 1.0 kg), pulse rate, and systolic blood pressure. Extrapyramidal symptoms scores were comparable between groups. Risperidone was well tolerated and efficacious in treating behavioral symptoms associated with PDD in children.